School Counselors Share Their Favorite Group Activities: A Guide to Choosing, Planning, Conducting, and Processing - Foss, Louisa L.; Association for Specialists in Group Work (Association for Specialists in Group Work, 2008)
Keywords: Educational counseling; Group counseling for children; Group counseling for teenagers; Activity programs in education; dept.csp; faculty_collection

Social competence, social support, and academic achievement in minority, Low-Income, urban elementary school children - Elias, Maurice J; Haynes, Norris M (School Psychology Quarterly, 2008)
Despite living in disadvantaged urban communities experiencing social and economic hardships, many children emerge with positive outcomes. Social-emotional competence and social support were hypothesized to have strong influences on academic trajectories during the critical period of academic skill acquisition. Participants were 282 third-grade students from six elementary schools in a Northwestern urban community. Beyond the importance of prior levels of academic competence, considerable variance in end-of-year academic outcomes was predicted by initial levels of academic social-emotional competence and improvements in social-emotional competence and perceived teacher support over the course of the year. Noteworthy is that findings were strongest for African-American students, but methodological caveats regarding research with underachieving minority youth were discussed. The findings suggest that school psychologists and others designing interventions to improve achievement of disadvantaged students should address social-emotional competencies and classroom climate, especially teacher support of students.
170 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/046-548-958-283-276 tex.type: [object Object]
Keywords: academic underachievement; dept.csp; prevention; resilience; social-emotional competence; urban minority youth